Spatial Information Theory 10th International Conference, COSIT 2011, Belfast, ME, USA - Egenhofer, Max J.; Giudice, Nicholas; Moratz, Reinhard; Worboys, Michael (Theoretical Computer Science and General Issues, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Spatial Information Theory, COSIT 2011, held in Belfast, ME, USA, in September 2011. The 23 revised full papers were carefully reviewed and selected from 55 submissions. They are organized in topical sections on maps and navigation, spatial change, spatial reasoning, spatial cognition and social aspects of space, perception and spatial semantics, and space and language.